Pengaruh Perilaku Kepemimpinan, Keadilan Kompensasi, Dan Kepuasan Kerja Terhadap Komitmen Organisasi (Studi Pada Pegawai Kantor Pelayanan Pajak Pratama Manado ) - Katuuk, Frets David (JURNAL RISET BISNIS DAN MANAJEMEN, 2015)
The aim of this research is to analyze the influence of Leadership Behavior, Fairness of Compensation, and Job Satisfaction on Organizational Commitment of the employees in Kantor Pelayanan Pajak (KPP) Pratama Manado. The findings show that Leadership Behavior, Fairness of Compensation, and Job Satisfaction have positive significant effects on organizational commitment of the employees in Kantor Pelayanan Pajak Office (KPP) Pratama Manado. While job satisfaction is the variable with the highest contribution on organizational commitment. Therefore job satisfaction is the most dominant variable on organizational commitment. Keywords: Leadership Behavior, Fairness of Compensation, Job Satisfaction, Organizational Commitment